A STUDY ON THE ABILITY OF THE SECOND YEAR STUDENTS OF SMA NEGERI 1 BANGUN PURBA ROKAN HULU IN COMPREHENDING ANALYTICAL EXPOSITION TEXTS - Khairul Umam; Fadly Azhar; Erni Erni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This descriptive research was aimed to find out the ability of the second year students of SMA Negeri 1 Bangun Purba Rokan Hulu in comprehending analytical exposition texts. The research data were collected in September 2017. The subject of this research was class XI Nature Science 1 which consisted of 23 students. The data were collected by administering a test to the students in the form of multiple choice test. The test contained 40 items. Based on the data analysis it was found that the highest score obtained by the students was in the aspect of finding factual information with the mean score of 74 (good level), and the lowest score was in the aspect of identifying social function with the mean score of 51 (mediocre level). As a conclusion, the ability of the second year students in comprehending analytical exposition texts was in good level (mean score 65.5). So, it is recommended that the students must be given more practice and read books in order to improve reading skill, especially in identifying social function, this is due to the fact that the students got lowest score in that aspect. And for other researchers are recommended to conduct another research design about analytical exposition text.Key Words: Students’ ability, analytical exposition texts